How perceptions of parents’ parenting behaviors pave the way to somatic symptoms: the mediating role of emotion regulation among adults - YILMAZ, TUĞBA (My University, 2023)
The purpose of this study was to investigate adult participants’ reflections on their parents’ parenting behaviors during childhood (parental overprotection and parental rejection), and their current emotion-regulation strategies and somatic symptoms. The study consisted of 627 participants and Somatization subscale of the Symptom Checklist-90-Revised, Difficulties in Emotion Regulation Scale and Short EMBU Children Form were given to the participants. Four different multiple mediation analyses were conducted to test mediator roles of emotion regulation difficulties between perceptions of the parenting behaviors (parental overprotection and rejection) and somatic symptoms among adults. Participants’ lack of goals and lack of strategies while dealing with negative emotions mediated the relationship between mother/father rejection and somatic symptoms. However, only participants’ lack of strategies while dealing with negative emotions mediated the relationship between mother/father overprotection and somatic symptoms. As a clinical implication, problem-focused coping strategies may assist adults with somatic symptoms. Also, mental health practitioners may focus on perceptions of overprotective and rejecting parental behaviors while formulizing somatic symptoms of the adult patients. Findings, strengths and limitations of this study were discussed in the light of the literature.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; Temel Bilimler (SCI); Natural Sciences (SCI); PSYCHOLOGY; Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; General Psychology; Social Sciences & Humanities; emotion regulation; parental overprotection; parental rejection; Somatic symptoms